Incidence of Gastritis with Erosive Gastritis at Adam Malik Hospital - Azzahra Indra P, Tabitha; Sopacua, Erwin; Maya Wardhani M. Biomed, Fiska (Jurnal Multidisiplin Indonesia, 2024)
Gastritis is inflammation or bleeding mucosa in the stomach that can be acute and chronic. Erosive gastritis can cause erosion stomach Because it damages the mucosa of the stomach, which can happen when you drink alcohol, take NSAIDs, stress, or drink coffee. Complications from erosive gastritis that are not treated can develop with age, starting from puberty until age. Based on the explanation background above, formulation problems in research This is incidence gastritis with erosive gastritis. General objectives of the research This is to know the incidence of gastritis with erosive gastritis. For RSU, Adam Malik Medan's Research results can give donation mind and increase service health to patients with erosive gastritis. Research results show that most gastritis patients at Adam Malik Hospital are aged 10-25, and categories aged 55-65 (24.6%). Research results show that patients with erosive gastritis at Adam Malik Hospital mucosa hyperemia (59%). Research results show a significant relationship between gastritis and erosive gastritis at Adam Malik Hospital (p0.000). Based on the results of the study, it can be concluded that: 1. Age Most gastritis patients at Adam Malik Hospital are aged 10-25 and categories aged 55-65 years (24.6%). 2. Majority of various types of patients sex female (57.4%) 3. Patients diagnosed with gastritis at Adam Malik Hospital (59%) 4. Patients with erosive gastritis at Adam Malik Hospital have mucosa hyperemia (59%) 5. There is a significant relationship between gastritis and erosive gastritis at Adam Malik Hospital (p0.000).